Універсальне офіційне звертання до сучасного українського військовика (втрати, здобутки, перспективи) - Скаб, Мар’ян (My University, 2018)
In the article, the main regularities, processes and tendencies of the formation of a modern universal address to the Ukrainian military are determined together with the description and analysis of extremely topical general problems of Ukrainians in the search of universal etiquette address. Actuality of the research lies in solving current topical problems of communication between Ukrainian servicemen. The author disputes the widely spread thesis about the use by the Cossacks and other Ukrainian national military formations of the address ”tovaryshu” as a universal official address, discusses the main cases of the use of compound nominations of the speech addressee with the components ”pane” and “tovaryshu”, proves the expediency of the official use in the Ukrainian army of the address “pane” as a partial manifestation of the nationwide universal etiquette nomination of the speech addressee. Conclusions and recommendations made can be used to improve and unify communication between Ukrainian military personnel
Universal Official Address to the Modern Ukrainian Military Personnel (Losses, Achievements, Perspectives).